Whole Genome Sequencing, Antibiotic Resistance, and Epidemiology Features of Nontyphoidal Salmonella Isolated From Diarrheic Children: Evidence From North China - Zhao, Wei; Li, Xin; Shi, Xuening; Li, Kewei; Shi, Ben; Sun, Jingyu; Zhao, Chao; Wang, Juan (Frontiers in Microbiology, 2022)
Nontyphoidal Salmonella((NTS) in children remains a growing burden on public health and often causes children to hospitalize with diarrheic symptoms. In this work, 260 strains of human Salmonella isolated from Jilin, China were characterized by serotypes, antimicrobial resistance using whole genome sequencing (WGS). The most prevalence serotype was S. Enteritidis (47.3%), followed by S. 1,4,[5],12:i:-)(33.1%) and S. Typhimurium(7.3%). And the consistency between resistance phenotype and genotype was confirmed. Correspondingly, strains harbored blaTEM-1B and tet(A) genes were detected, which verified the level of resistant phenotype in β-lactams and tetracyclines. The presence of single mutation in parC and gyrA and qnrS1 gene corresponding to quinolones was also observed. In our work, multilocus sequence typing (MLST) and core genome sequence typing (cgMLST) was found to be a high resolution to molecular traceability, and the combination of both was conductive to practical application with actual situation. Taking all above into consideration, we suggested that the comprehensive surveillance of Salmonella infection in children should be carried out to monitor antimicrobial resistant trend from various sources and alert outbreaks of foodborne diseases to protect public health.